Master's Student 3++: Portrait and New Requests - I. N. Burkova (Moscow Polytechnic University, 2022)
The exclusion of Russia from the Bologna process led to large-scale discussions in society about the future of the Russian magistracy. The implementation of master's education raised questions throughout 29 years of its existence. Society has developed a perception of magistracy as a problem area of higher education. Thus, when the question arose about the advisability of developing a master's programs after Russia's exit from the European Higher Education Area, the majority formed their opinion: no magistracy - no problems. However, objective data allow us to see the situation in the different perspective.The paper presents the result of a study of the qualitative and quantitative composition of students of the domestic master's programs from 2012 to 2020. Based on the analysis, the main trends in changing the profile of Russian master's students have been identified. The tasks relevant to the development of the institute of the Russian magistracy are outlined with a focus on a portrait of today's master's student.The analysis shows that the magistracy has firmly occupied the niche formed in recent years for the training and retraining of specialists. It has become an independent institution of higher education with its own goals, objectives, resources and, most importantly, with its own contingent. The magistracy has a small inertia in response to the emerging challenges of society. Because of that the magistracy increases its demand every year. At the same time, its self-sufficiency rises.The magistracy has been long and hard embedded into the Russian traditions of education. Finally, it has found its place. The factors considered in the study allow us to speak about the high potential for the Russian magistracy development.The data and conclusions presented in the study can serve as the basis for a scientific discussion about the future of domestic education.